Initial Post-Market Experience of the Penumbra System: Revascularization of Large Vessel Occlusion in Acute Ischemic Stroke in the United States and Europe - Vinall, Maria (MD Conference Express, 2009)
The Penumbra System is a mechanical clot removal device that is indicated for the revascularization of occluded large vessels in acute ischemic stroke. It has been approved for commercial use in the United States and Europe. In a postmarket study to assess its safety and effectiveness in a “real world” setting, the performance of the device was deemed to be comparable with the results of the pivotal Penumbra trial with regard to revascularization rate, incidence of adverse events, intracerebral hemorrhage, all-cause mortality, and 90-day good functional outcome.